PELAKSANAAN ZAKAT PERTANIAN (STUDI KASUS PETANI BAWANG DI NAGARI KAMPUNG BATU DALAM KECAMATAN DANAU KEMBAR KABUPATEN SOLOK) - WIDI NOPIARDO; AFRIANI AFRIANI; RIZAL FAHLEFI (Al-Masraf: Jurnal Lembaga Keuangan dan Perbankan, 2018)
This paper discusses the implementation of agricultural zakat in "Nagari Kampung Batu Dalam, Kecamatan Danau Kembar, Kabupaten Solok" and what are the constraints faced by the community in the implementation of agricultural zakat. The type of research is field research. It is concluded that the implementation of zakat onion farming is done by farmers at every harvest time, two to three times of harvest and the month of Ramadan. The amount of zakat disbursed partially calculates the operational costs and partly focus on the amount of crops obtained. Zakat is distributed in the form of money and goods and onions are given to workers who are deemed entitled to receive zakat, kinsman relatives, orphans and zakat are also channeled to the mosque or local mushalla. Some people still equate agricultural zakat with alms or infak. While the constraints faced by the community in implementing agricultural zakat is the level of public awareness is still low, it is influenced by the lack of understanding of society about agricultural zakat and education is still low, the distribution of zakat that has not been right target and the absence of institutions that collect and distribute zakat.